Penerapan Media Komik Tanpa Teks Terhadap Keterampilan Menulis Cerita Pendek Siswa Kelas III SD Panancangan 2 Kota Serang - Hakim, Zerri Rahman; Handayani, Ellin (Indonesian Research Journal on Education, 2022)
The research was conducted because there were problems in the form of many students still havingdifficulty in making word for word to make a story, students also still had difficulty in determining thetheme, plot, characters, and setting used to make a story. And students also still find it difficult to make a story that has a unified story. This is triggered because at the time of giving the writing assignment the teacher does not directly determine the theme or title of the story that must be written by the students, while most students have difficulty in determining what theme to choose. Most teachers also do not use learning media so that it is easier for students to make a story. The purpose of this study wasto determine the learning outcomes of third grade students at SDN Panancangan 2 on simple essaywriting material, carried out in August 2017. The data collection technique was by doing tests, andnon-tests. The research method used is quasi-experimental with the research sample being grade III B and III A students with purposive sampling technique. The average pretest in the experimental class was 44.56 while in the control class it was 55.60. The control class and the experimental class have significantly different learning outcomes, this is after the learning process using comics media without text in the experimental class obtained an average posttest of 64.10 while in the class using image media the control class was 58.37. So it can be concluded that the students' short story writing skills that were carried out in the experimental class using comics without text were better than the control class that did not use learning media.